2006
DOI: 10.1021/jm060077j
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of SCH446211 (SCH6):  A New Ketoamide Inhibitor of the HCV NS3 Serine Protease and HCV Subgenomic RNA Replication

Abstract: Introduction of various modified prolines at P(2) and optimization of the P(1) side chain led to the discovery of SCH6 (24, Table 2), a potent ketoamide inhibitor of the HCV NS3 serine protease. In addition to excellent enzyme potency (K(i)*= 3.8 nM), 24 was also found to be a potent inhibitor of HCV subgenomic RNA replication with IC(50) and IC(90) of 40 and 100 nM, respectively. Recently, antiviral activity of 24 was demonstrated with inhibition of the full-length genotype 2a HCV genome. In addition, 24 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 30 publications
0
61
0
Order By: Relevance
“…However, they may be difficult to depict, based solely on sequence examination, if, similarly to TRIF and CARDIF, they diverge from the consensus NS3/4A cleavage sequence. The highly specific productbased macrocyclic NS3 protease inhibitor BILN 2061 [74] and the less toxic new generation of another class of NS3 inhibitors, referred to as electrophilic or serine-trap inhibitors, such as VX-950 [75] and SCH6 [76] , probably exert their high inhibitory effect on HCV infection, not only by preventing HCV expression [77] but also by preventing NS3/4A to interfere with IFN induction.…”
Section: Ifn Inducing Pathwaysmentioning
confidence: 99%
“…However, they may be difficult to depict, based solely on sequence examination, if, similarly to TRIF and CARDIF, they diverge from the consensus NS3/4A cleavage sequence. The highly specific productbased macrocyclic NS3 protease inhibitor BILN 2061 [74] and the less toxic new generation of another class of NS3 inhibitors, referred to as electrophilic or serine-trap inhibitors, such as VX-950 [75] and SCH6 [76] , probably exert their high inhibitory effect on HCV infection, not only by preventing HCV expression [77] but also by preventing NS3/4A to interfere with IFN induction.…”
Section: Ifn Inducing Pathwaysmentioning
confidence: 99%
“…The P2 benzene ring has been macrocyclized with the P3 capping group through an aryl-alkyl ether linkage to depeptize the P2-P3 moiety [28]. These are the conformationally preorganized inhibitors with better stability and strong potency [28][29][30]. Recently, a series of potent tripeptide truncated at the N-terminus from some hexapeptide ketoacid inhibitors are described to explore the P2-P3 binding features [31].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Several NS3/4 protease protease inhibitors (PIs) have been developed to block this step of the viral life cycle and have been proved, in some cases, to significantly decrease the plasma viral load of infected individuals. [8][9][10][11] Since the first description of HCV, numerous studies have described the HCV variability found in infected individuals. 12,13 The observed HCV heterogeneity, like other RNA viruses, originates from the high rate of incorrect nucleotide substitutions during viral RNA replication (10 Ϫ4 -10 Ϫ5 mutations per nucleotide and per replication cycle) 14 and rapid viral turnover (producing on average 10 12 virions per day in infected individuals).…”
mentioning
confidence: 99%